Acute Lupus Pneumonitis with Cytomegalovirus Co-infection in Patients withLupus Nephritis - Hadi Kurniawan Wijaya (Indonesian Journal of Rheumatology, 2024)
Introduction: Most patients with systemic lupus erythematosus (SLE) showsigns of pulmonary involvement. The clinical manifestations of LupusPneumonitis are the similar to those of acute interstitial pneumonia. The useof cyclophosphamide in lupus nephritis (LN) is associated with high CMVtiters. Ganciclovir is the main choice of therapy for CMV pneumoniainfection. Case presentation: A 19-year-old female with previous history oflupus nephritis presented with worsening dyspnea, productive cough withyellowish sputum and hemoptysis. Following physical, laboratory andradiological examinations, the patient was diagnosed with acute lupuspneumonitis, with a differential diagnosis of pneumonia infection. Duringtreatment in the intensive care unit (ICU), she was put on ventilator andreceived routine hemodialysis due to pulmonary edema. She was givenintravenous antibiotics before the culture results came out, but there wasno clinical improvement. Once the culture results returned negative, theantibiotics were discontinued and IV pulse methylprednisolone was started.There was significant clinical, radiological, and laboratory improvements.After discharge, the patient experienced hemoptysis again due to CMVpneumonia infection and was given ganciclovir therapy with satisfactoryresults. Conclusion: In patients with advanced LN and pulmonaryinvolvement, distinguishing between infection and SLE flares may bechallenging, which can cause dilemma in diagnosis and treatment decisions.Adequate oxygenation with ventilator, hemodialysis, and administration ofganciclovir and mycophenolic acid provides significant improvements inpatient care.